Next-Generation Computational Approaches for Biological Network Analysis - Hamza Ali Mari; Maham Taqi; Abrar Ahmed Rattar; Ahsan Jamal Memon; Muhammad Talha Nasir; Arleen Yousuf (BioMed Target Journal, 2025)
Protein-protein interaction (PPI) networks are critical to understanding cellular processes and disease mechanisms. Computational advances have transformed PPI analysis, allowing for the prediction, analysis, and visualization of intricate interaction networks. This article discusses the basics of PPI networks, experimental and computational methods for their detection and analysis, and novel predictive models. We cover sequence-based approaches, such as homology, domain, and motif-based methods, as well as structure-based methods like structural alignment, comparison, and interface-based prediction. Functional annotation-based methods, such as Gene Ontology (GO) annotations, pathway-based methods, and co-expression data, are also discussed. Machine learning methods, such as supervised and unsupervised models, neural networks, and deep learning, increasingly contribute to improving PPI predictions. In addition, network inference methods, including Bayesian networks, graph-based approaches, and integrative multi-omics strategies, extend our understanding of biological systems. Key applications of PPI networks are the prioritization of disease genes, annotating uncharacterized proteins' functions, analyzing pathways, and discovering biomarkers. Yet, incompleteness and noisiness of data, false positives and negatives, and scalability limitations of computational methods continue to pose problems. Emerging directions highlight upcoming technologies, advances in machine learning, and multi-omics integration with the potential for steering personalized medicine and precision health.